PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN PELALAWAN PADA MASA PANDEMI COVID-19 - T. AFWAN GHAFUR (Badan Penelitian dan Pengembangan Daerah Kab. Pelalawan, 2023)
This research aims to determine the influence of the work environment on employee performance at the Personnel and Human Resources Development Agency during the Covid-19 pandemic. The number of samples in this study were 26 respondents. The respondents in this study were employees who worked at BKPSDM. The method of this research is quantitative research. Data collection techniques in this study were carried out by giving questionnaires to respondents. In proving and analyzing this, validity and reliability tests, classical assumption tests, multiple linear regression tests and f (simultaneous) and t (partial) tests are used. The test results show that: The results of testing the model simultaneously (simultaneously) on each variable, namely work environment factors on individuals, psychology, organization, and performance show that the calculated F value is greater in the F table with a small significance than 0.05. Therefore, it can be concluded that the work environment simultaneously influences the work environment. Furthermore, the partial T test shows that each variable obtains a significance of 0.000 <0.05, meaning that there is an influence of the work environment on individual, psychological, organizational and work environment factors. Therefore, it can be concluded that the alternative hypothesis on each variable is accepted.